Modification of jet shapes in PbPb collisions at root s(NN)=2.76 TeV - Chatrchyan, S. (2014)
The first measurement of jet shapes, defined as the fractional transverse momentum radial distribution, for inclusive jets produced in heavy-ion collisions is presented. Data samples of PbPb and pp collisions, corresponding to integrated luminosities of 150 mu b(-1) and 5.3 pb(-1) respectively, were collected at a nucleon-nucleon centre-of-mass energy of root s(NN) = 2.76 TeV with the CMS detector at the LHC. The jets are reconstructed with the anti-k(T) algorithm with a distance parameter R = 0.3, and the jet shapes are measured for charged particles with transverse momentum P-T > 1 GeV/c. The jet shapes measured in PbPb collisions in different collision centralities are compared to reference distributions based on the pp data. A centrality-dependent modification of the jet shapes is observed in the more central PbPb collisions, indicating a redistribution of the energy inside the jet cone. This measurement provides information about the parton shower mechanism in the hot and dense medium produced in heavy-ion collisions. (C) 2014 The Authors. Published by Elsevier B.V.